In-season effect of a combined repeated sprint and explosive strength training program on elite junior tennis players - Fernandez-Fernandez, J.; Sanz-Rivas, D.; Kovacs, M. S.; Moya, M. (The Journal of Strength and Conditioning Research, 2015)
The aim of this study was to analyze the effects of a combined explosive strength (ExpS) and repeated sprint (RS)-training program (2 times per week) on performance (sprint, jumping ability, and RS ability [RSA]) in young elite tennis players during a competitive period. Eight competitive internationally ranked male junior tennis players participated in an 8-week training intervention. After training, except for percentage of decrement in the RS test (p = 0.72) and maximal aerobic performance (p = 1.0), all performance variables (i.e., sprint, countermovement jump, and RSA) were significantly improved (p = 0.05; effect sizes ranging from 0.56 to 1.12). Although one can expect greater effects of ExpS or RS training programs alone than a combined program, the results obtained here show that the inclusion of a combined ExpS and RS training program seems to be an effective training tool to improve neuromuscular performance (i.e., changes in jumping ability and single sprint) as well as RSA in high-level tennis players.